On-chip irreversible electroporation for bacterial cell membrane rupture - S. Jaikla (2018)
In this work, the DNA preparation process for genetic analysis was developed. To rupture the cell membrane of Salmonella on a microfluidic chip, high electric field pulses were applied through gold electrode. The applied voltage was less than 10V DC voltage. Electric field pulses were short-duration in microsecond. Fluorescent spectrophotometer was employed for live/dead bacterial cells detection. The live bacterial cells were tagged by SYTO 9 green fluorescent stain. The red-fluorescent nucleic acid stain, propidium iodide was used to tag the dead cells. The highest percentage of 95% dead cells was at 7V applied voltage and 90 μs pulse duration. This result was confirmed by plate count with completely dead cell. ©2012 IEEE.